Social studies teachers estimate the degree of application of crisis management in government schools in the Kasbah District of Irbid - Migdadi, Mohammad Ahmad Mohammad (Journal of Risk and Crisis Management, 2020)
The current study aimed to reveal the estimates of social studies teachers for the degree of application of crisis management in government schools in the Irbid Kasbah brigade, and to identify the significance of the differences in the estimates of social studies teachers about the degree of application of crisis management in government schools in the Kasbah brigade according to the gender variable, the study was applied In the second semester of 2020 AD, an analytical descriptive approach was used. The study population consisted of social studies teachers in government schools in the Kasbah District of Irbid, and the study sample consisted of (124) male and female teachers, and the number of male sample members reached (68). The number of females reached (56), who were chosen by simple random method. The study concluded the following results: the arithmetic averages ranged between (3.53- 4.70), where paragraph (1) stipulated that “the manager calls the competent authorities to provide all information to the crisis management team” in the first rank and with an arithmetic average of (4.70), while it came in the last rank Paragraph (9), which reads: “The manager works to limit the material and human losses resulting from the crisis, ” with an average of (3.53). The mean of the degree of application of crisis management in public schools in Jordan as a whole was (4.19) And to a (great) degree, There were no differences in the estimates of the sample individuals on the means of the tool as a whole according to the gender variable (male, female).In light of the results, the researcher presented the following recommendations: Provide adequate support to the Ministry of Education in order to maintain its continuity and its ability to manage crises. Support to national projects that help to manage crises well, Make effective future plans to cope with natural crises and various disasters, Carrying out more studies and researches on different samples and stages.
Keywords: Estimates of social studies teachers; degree of application of crisis management; government schools; Irbid Qasbah District